Privacy and Safety in Online Learning - Quintel, Denise FitzGerald; York, Amy (MT Open Press, Middle Tennessee State University, 2023)
This collection features essays, case studies, and pedagogical approaches that explore how educators managed the privacy, security, and safety concerns that rushed into our lives as we shifted into emergency remote learning in 2020. While the COVID-19 pandemic brought this concern into focus, privacy issues with online learning continue to exist alongside us and our students. This book provides readers insight into the current state of privacy issues, describes the challenges and rewards of developing more privacy-focused learning environments, and presents several resources and tools that readers can bring to their own teaching practices. Representing a variety of perspectives from K-12, higher education, and libraries, contributors describe the challenges they encountered and offer solutions to help ensure the safekeeping of students' online lives. How do we navigate these online environments, who collects our data, and how can we protect our most vulnerable populations?